2021
DOI: 10.3390/curroncol28010062
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Patient-Centred Research in the Canadian Cancer Trials Group

Abstract: The inclusion of patients as partners in research is a key link in the delivery of patient-centred care in healthcare systems. Despite genuine intentions to engage patients in authentic partnerships, efforts can result in tokenism and benefits of engagement are missed. Understanding how patient engagement provides value along the research to patient-care continuum and how to best engage patients as partners are key. This document describes the method taken by the Canadian Cancer Trials Group (CCTG) to implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The literature was predominantly based in the UK (35%, n=18),24–41 USA (24%, n=12)16 42–52 and Canada (20%, n=10) 53–62. The remaining studies (22%, n=11) were based in multiple countries (8%, n=4),63–66 Australia (4%, n=2),67 68 Denmark (4%, n=2), Ireland (2%, n=1),69 Japan (2%, n=1)70 and Norway (2%, n=1) 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature was predominantly based in the UK (35%, n=18),24–41 USA (24%, n=12)16 42–52 and Canada (20%, n=10) 53–62. The remaining studies (22%, n=11) were based in multiple countries (8%, n=4),63–66 Australia (4%, n=2),67 68 Denmark (4%, n=2), Ireland (2%, n=1),69 Japan (2%, n=1)70 and Norway (2%, n=1) 71.…”
Section: Resultsmentioning
confidence: 99%
“…Of the extracted literature, 69% (n=35) were empirical, and the remaining 31% (n=16) were non-empirical. Of the empirical studies, the majority were qualitative in nature (54%, n=19),28 30 34 35 37 38 44 47 49 56 59 60 64 67–69 71–73 followed by mixed methods (29%, n=10),26 31 32 40 51 52 54 58 62 66 and then quantitative (17%, n=6)42 46 53 55 65 70 study designs. We will now explore findings based on the specific research objectives of this review.…”
Section: Resultsmentioning
confidence: 99%
“…With this focus on patient and public involvement, the CCTG has improved their trial enrollment and activity, noting the highest accrual and activity data in years. 26 This highlights the importance of patient involvement and autonomy in their care, regardless of the platform. It is suggested that DCTs incorporate these patient-centered principles to facilitate inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…27 Hence PCR is a collective good justified by COMMENTARY | 735 the rhetoric of public accountability, 28 and likewise justifying its public funding and merit by assessment using approved metrics of 'person-centredness' and by submission to social control and governance by 'Royal Science'. 29…”
Section: Governmentality and The Academymentioning
confidence: 99%
“…Research elites comprising ‘Royal Science’ attain power over the research by providing an alternative solution and rationality to ‘legitimate the concrete use of power’ 27 . Hence PCR is a collective good justified by the rhetoric of public accountability, 28 and likewise justifying its public funding and merit by assessment using approved metrics of ‘person‐centredness’ and by submission to social control and governance by ‘Royal Science’ 29 …”
Section: Governmentality and The Academymentioning
confidence: 99%